2017
DOI: 10.2147/copd.s131868
|View full text |Cite
|
Sign up to set email alerts
|

Platelet distribution width as a prognostic factor in patients with COPD – pilot study

Abstract: BackgroundPlatelets may actively participate in inflammation in COPD. Platelet distribution width (PDW), a measure of platelets’ volume heterogeneity, may increase in platelets’ activation. We hypothesized that PDW may be a marker of hypercoagulation, which plays a significant role in conditions associated with worse survival of patients with COPD, eg, acute myocardial infarction and other forms of ischemic heart disease.MethodsRetrospective analysis of 79 patients. Variables were compared after grouping patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
1
14
1
1
Order By: Relevance
“…Our most interesting finding is the demonstration of prognostic significance of higher values of PDW on admission in internal medicine wards. Higher PDW levels have recently been reported to be associated with increased morbidity and mortality in numerous clinical investigations that focused on patients with critical illness [11,13], and with specific acute and chronic disorders [10,[14][15][16][17][18][19][20][21][22][23]. We observed that PDW values above the cut-off of 16.7% at admission, as well as above the normal range, were associated with an increased risk of mechanical ventilation and death during the current hospitalization, and shortened survival following discharge.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our most interesting finding is the demonstration of prognostic significance of higher values of PDW on admission in internal medicine wards. Higher PDW levels have recently been reported to be associated with increased morbidity and mortality in numerous clinical investigations that focused on patients with critical illness [11,13], and with specific acute and chronic disorders [10,[14][15][16][17][18][19][20][21][22][23]. We observed that PDW values above the cut-off of 16.7% at admission, as well as above the normal range, were associated with an increased risk of mechanical ventilation and death during the current hospitalization, and shortened survival following discharge.…”
Section: Discussionmentioning
confidence: 52%
“…Increased PDW values have been reported in patients with diabetes mellitus [5], cancer [6,7], and cardiocerebrovascular and respiratory disorders [8][9][10][11][12]. Moreover, higher PDW levels have recently been reported to be associated with increased morbidity and mortality among patients with critical illness [11,13], coronary artery disease [14][15][16][17], cancer [18][19][20][21], pulmonary embolism [10,22], and chronic obstructive pulmonary disease [23]. Most previous studies on the clinical significance of PDW involved patients with specific disorders.…”
Section: Introductionmentioning
confidence: 99%
“…14 Further evidence suggests that elevated PDW is associated with worse respiratory function and reduced survival in patients with stable COPD. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…14 PDW is expected to be higher in COPD patients compared to healthy people. 14 There are studies showing that PDW is correlated with increasing age and MPV. 15 In our study, there is a reverse finding for PDW.…”
Section: Discussionmentioning
confidence: 99%